RINTISAN SMART VILLAGE MELALUI PROGRAM PEMBERDAYAAN MASYARAKAT DESA KEMANTAN - Dedek Helida Pitra; Zulqoidi R. Habibie; Arisman Sabir; Titis Wulandari; Zirul Habibi (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
The goal of developing a smart village (Smart Village) in the village of Kemantan, is for village development based on community empowerment that is inclusive and sustainable through increasing human resources. Community service is carried out by transforming the way of thinking, and how the community works in improving the quality of life, economy, skills, expertise, management, and governance of Kemantan Village in the Digital Age. The method used in the implementation of this community service is carrying out the method of implementing activities in the form of training, followed by discussions and questions and answers as well as the Socialization / Counseling method. With this, this activity can contribute and benefit in increasing the competitiveness and economy of the community. The results of community service activities, including the Village Children's Smart Home (RUMCADES) in Kemantan Village, making a Living Pharmacy (TOGA) PKK for the Kemantan Village Community, Village Community Arrangement, and Services. The community empowerment strategy is manifested in development as part of an effort to realize smart village pilots in a participatory way to anticipate economic crises, money politics, and necessities of life.